Response of a RC bridge in WA to simulated spatially varying seismic ground motions - Hao, Hong; Chouw, N. (Engineers Media, 2008)
In this paper, numerical results from a non-linear dynamic response analysis of a 50 m long two-span RC bridge in the Perth Metropolitan Area (PMA) to simulated spatially varying seismic ground motions are presented and discussed. Spatially varying ground motions are stochastically simulated to be compatible with the design spectrum for different site conditions given in the Draft Australian Earthquake Loading Code, and are compatible with an empirical coherency loss function representing highly, intermediately and weakly correlated spatial ground motions. Effects of ground motion spatial variation, bridge bearing stiffness, gap size of the expansion joint, and soil stiffness on impact force between the girders, and bending moment and shear force of the pier are investigated. Discussions on the influence of ground motion spatial variations on bridge structure response are made.